Clinical course of chronic hepatitis B (CHB) presented with normal ALT in Asian American patients. Issue 10 (22nd January 2015) - Nguyen, K.; Pan, C.; Xia, V.; Hu, J.; Hu, K.‐Q.
Summary The clinical course for chronic hepatitis B (CHB) patients with normal ALT and with or without minimal histologic activity remains unclear. We assessed frequency, amplitude, disease activities, and associated factors of ALT and/or AST flares in this subpopulation. Forty‐seven consecutive treatment naïve Asian patients with CHB were enrolled from two liver clinics between December 2003 and January 2013, who had normal baseline ALT by routine clinical biochemical testing performed 6 weeks before or after the liver biopsy. We defined a flare as elevation of ALT/AST above the upper limit of normal of ALT/AST. The mean follow‐up was 37.6 (CI = 12, 88) months, and the mean age at entry into the study was 43.3 (CI = 19, 65); 22/47 (46.8%) were males; 15/45 (33.3%), HBeAg+; 68.1% had stage 0–1 fibrosis; 63.8% had grade 0–1 inflammation. During follow‐up, 13/47 (27.7%) cases developed ALT flare at least once in a mean of 13.5 (CI = 2, 43) months after liver biopsy; ALT flare was not associated with baseline ALT level, fibrosis stage, inflammation grade, hepatitis B virus (HBV) DNA load, HBeAg status, HBV genotype, HBV precore and basal core promoter mutations. 11/13 (84/6%) of ALT flares resolved during follow‐up. 13/13 (100%) of ALT flares met AASLD treatment criteria, but only 6/13 (46.2%) were on HBV treatment. Serum ALT and/or AST flares occur frequently in CHB carriers who initially presented with normal ALT during pretreatment period. Thus, regular follow‐up is warranted despite status of ALT/AST. No clinical factors were found to be associated with ALT flares.